Analisis Perkembangan Karakter Tokoh Dalam Novel Kami Bukan Sarjana Kertas Karya J. S Khairen - Desra Nita Tampubolon; Elferina Yanti Siregar; Emasta Evayanti Simanjuntak; Frinawaty Lestarina Barus; Josepin Putri Nadya Purba; Perdana Gemilang Manurung (Universitas Palan, 2023)
This study aims to describe the development of the characters and describe the implementation of research in learning Indonesian at school. The research method used is descriptive method with qualitative research. The approach used is a behavioristic psychology approach. The data source used is a novel Kami Bukan Sarjana Kertas by J. S Khairen. So the development of the characters in the novel is Ogi who is the main character in the novel Kami Bukan Sarjana Kertas by J.S. Khairen thus became a central figure. Ogi's character is a developing character based on words, actions, physical depictions of characters, and direct lighting. Ogi is considered a developing character because there are changes and developments in the character that appear in line with the development of the events or incidents narrated in the story at the beginning of the story. Ogi is a lazy person, but after experiencing many things, Ogi is determined to change for the better. The second character that the researcher analyzed, namely Gala, is a supporting character in the novel Kami Bukan Sarjana Kertas by J.S. Khairen. Gala has the character of a protagonist. At first, Gala's character was a fighter who had a strong determination to succeed, but due to several things that didn't match her expectations, Gala became selfish and disobedient. However, in the next arc, Gala decides to obey and not be selfish anymore. The third figure that the researcher analyzes is Ayah Gala. Gala's father is a supporting character in the novel Kami Bukan Sarjana Kertas by J.S. Khairen. Gala's father has an antagonistic nature. A gala father likes to impose his will on others without realizing that what has been done to his son is gala. But in the end, Gala's father changed and realized that Gala had been under pressure all this time.